Wound Care Treatment in A Case of Severe Scabies Crustacea in Patient with Stroke - Widyaningsih, Susana; Pratama, D. A; Isnaini, Nur (Sainteks, 2023)
Because of their lowered immunity and altered skin physiology, older persons are more susceptible to contracting scabies. In addition to immune system issues, aging is accompanied by changes in skin physiology, such as atrophy of the epidermis and dermis, hyperkeratosis, a diminished ability of the skin to protect against external assaults, and a delayed healing rate. A port of entry for infections is also the dry skin of the elderly. The purpose of this study is to identify the characteristic of scabies crustose patient, analyse the wound care interventions applied on patient with scabies crustose, and manage wounds in scabies crustose patients. This research was a case study is the process of assessing nursing care and analysing what interventions are given to patients for 4 days. The treatment was conducted in surgical ward, Dr. Soedirman hospital, Kebumen, Indonesia. The characteristics of the respondent in this case study is a 62-year-old woman with a diagnosis of Crustose Scabies. After treatment for 4 days, the condition of the patient’s wound gradually improved, the hyperkeratotic wound on the palm of the hand which had initially thickened gradually began to thin.